Природні барвники в матеріалах багатошарової мустьєрської стоянки Пролом ІІ - Степанчук, В.М.; Нездолій, О.І.; Вєтров, Д.О. (Археологія і давня історія України, 2018)
Статтю присвячено дослідженню серії фрагментів вохри, виявлених у мустьєрських шарах печерної стоянки Пролом ІІ у Криму. Наведено загальні відомості про стоянку та археологічний контекст природних барвників. Охарактеризовано основні
фізичні та метричні показники фрагментів барвників, систематизовано дані про ознаки навмисних модифікацій і пошкоджень. Finding natural pigments in the context of the cultural
layer of European Middle Palaeolithic sites has traditionally been associated with non-utilitarian activities
of the Neanderthals. The revision of materials of Prolom II revealed quite numerous ocher finds in
several Middle Palaeolithic layers. There is a reason to believe that pigments were supplied by the alluvium
of the Kuchuk-Karasu River, remote from the site at a minimal distance of a few tens of meters. Items in the
collection are mostly fragmented and demonstrate numerous signs of secondary processing. The fact of the
presence in the Middle Palaeolithic layers of Prolom II of a rather numerous series of artificially ground fragments
of mostly soft ocher, found near the site and intentionally brought to it, as a minimum, attests to
a certain interest of the Neanderthals to natural pigments. Natural pigments do not belong to the number
of vital items, therefore, the actions with which they were processed can not be explained by purely utilitarian
causes. Layers I—III are dated radiometrically and refer to span between 23 to 41 uncalibrated radiocarbon
thousands of years ago. Thus, the data we have obtained delivers new additional information to the general
fund of evidence on the non-utilitarian practices of the late Neanderthals of Eastern Europe.